The Animalistic World in V. S. Vysotsky’s Poetics - Namakshtanskaja, KInna E.; Romanova, Elena V. (Respectus Philologicus, 2003)
V. S. Vysotsky’s poetry distinguishes in its variety and amount of images. The poet presents the problems of human relations using realistic and symbolic images and placing them in real, mythological and fairy-tale situations. Thus, his text and context are built in a parallel way or interlace in some strophes and lines of his songs and poems. Touching upon themes of human relations, social, national and political organization of Soviet society and man’s place in it, V. S. Vysotsky makes use of different symbols, including images of birds and animals. The article deals with the analysis of semantic meaning reflected in the world of mythology, Bible, folk and phraseology. Besides, the article focuses on the author’s use of the presented images.